Establishment of rapid detection of Haemophilus influenzae type b by isothermal amplification of bexA gene - Siong, Leow Chee (Pusat Pengajian Kesihatan, 2015)
Haemophilus influenzae type b (Hib) is a common cause of childhood meningitis that leads to a significant morbidity and mortality in both developing countries and underdeveloped countries, where the successful Hib conjugate vaccine is not accessible. A rapid and costeffective diagnostic method was highly demanded in resource-limited laboratory. Hence, the aim of this study is to establish a rapid detection method for H. influenzae type b by loopmediated isothermal amplification (LAMP) of bexA gene. A LAMP primer set was specifically designed to target bex\ gene. An in-house LAMP reaction was established and optimized using extracted genomic DNA of Haemophilus influenzae ATCC 10211. Subsequently, both LAMP reagents and reaction conditions were optimized and the optimized LAMP assay was subjected to analytical specificity and sensitivity evaluation. PCR reaction was conducted by using outer primers to provide comparison in term of analytical sensitivity. The analytical specificity was evaluated with thirty non-haemophilus strains which showed 100% specificity for bexX gene identification. The limit of detection (LOD) for LAMP assay was determined at 2 pg of DNA per reaction and as low as 2 colonies-forming units (CFU) per reaction. This indicates that the detection limit of LAMP by CFU per reaction was 100 fold lower than the detection limit of PCR. Based on the result obtained, LAMP has the potential to become an excellent diagnostic tool capable to produce a rapid, highly sensitive and specific result in a single temperature condition.